Archives of Alalaḫ IV in Archaeological Context - Von Dassow, Eva 1965- (2005)
Written records, like other artifacts, were produced and used under particular circumstances that are usually reflected-if only indirectly-in the locations where they are found. However, the archaeological findspots of inscribed artifacts are often neglected in the study of the texts inscribed on them. Such has been the case with the cuneiform tablets found in C. L. Woolley's excavations at Alalaḫ. For over half a century, the Alalaḫ tablets have been utilized in historical and philological research with little consideration of their findspots, though these were duly recorded in the course of excavation. The present article collects the archaeological data pertaining to the tablets found at 15th-century Alalaḫ IV and reintegrates these data with the tablets' contents. On this basis the archives are reconstructed, described, and interpreted in terms of their spatial locations, prosopography, textual content, and chronology. This investigation reveals not only patterns of tablet use and storage, but hitherto unobserved aspects of the society that produced the tablets and the history to which they attest.